2019
DOI: 10.1167/iovs.18-24977
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Hypoxic Glial Cells in a Model of Ocular Hypertension

Abstract: PurposeReoxygenation after hypoxia can increase reactive oxygen species and upregulate autophagy. We determined, for the first time, the impact of elevated IOP on hypoxia induction, superoxide accumulation, and autophagy in a bead model of glaucoma.MethodOcular hypertension was achieved with magnetic bead injection into the anterior chamber. Before mice were killed, they were injected with pimonidazole for hypoxia detection and dihydroethidium (DHE) for superoxide detection. Total retinal ganglion cells (RGCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 62 publications
3
32
1
1
Order By: Relevance
“…4b, c). Hypoxic glia and RGCs were also reported after induction of ocular hypertension, suggesting the potential importance of hypoxia in glaucoma pathology 45,46 . RGC death did not necessarily occur in close proximity to major vessels after EDN1 insult, but it is possible that loss of blood flow or damage to minor vessels and capillary beds contributes to EDN pathology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4b, c). Hypoxic glia and RGCs were also reported after induction of ocular hypertension, suggesting the potential importance of hypoxia in glaucoma pathology 45,46 . RGC death did not necessarily occur in close proximity to major vessels after EDN1 insult, but it is possible that loss of blood flow or damage to minor vessels and capillary beds contributes to EDN pathology.…”
Section: Discussionmentioning
confidence: 98%
“…EDN ligands cause vasoconstriction by binding to EDNRA expressed by vascular smooth muscle cells 4,7,8,43,44 . Thinner retinal vessels and evidence of hypoxia have been demonstrated in animal models of chronic glaucoma 5,6,45,46 . Importantly, JUN was found be an important regulator of ischemia-induced neuronal death [47][48][49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent data showed that just an elevated IOP induced oxidative stress (via reduction in glutathione), axon degeneration of the optic nerve head and autophagy in the retinas. Thus, hypoxic glial cells can be detected in animals with OHT, even in the absence of a glaucomatous pathology (39). β2AR of astrocytes were also involved in the regulation of the glucose metabolism (40, 41) and are discussed to contribute to neuronal degeneration (42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Using a rat laser photocoagulation model of OHT, Chidlow et al 47 reported a highly variable degree of axon transport disruption and pimonidazole labeling that did not correspond statistically with the degree of IOP elevation. Furthermore, Jassim and Inman 23 observed no pimonidazole labeling in the retina 2 weeks after the induction of ocular hypertension in a mouse bead model of OHT; yet, cell loss was as great as 50% in some eyes. In this study, numerous pimonidazole-positive glia were detected at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 16 18 To our knowledge, we were the first to propose the use of paramagnetic microparticles that could be directed with a magnet to the iridocorneal angle, allowing for control of distribution and avoidance of disruption to vision through occlusion of the pupil. 19 We have since used this model to investigate RGC dendritic atrophy, 20 , 21 and others have adapted its use for mice, 22 , 23 but a detailed characterization of the rat model has yet to be performed. We use the Brown Norway rat ( Rattus norvegicus ) because (1) it is the rat genetic standard (and as such will allow for detailed -omics analysis (e.g., KEGG pathways based on Brown Norway gene annotations); (2) their temperament is amenable to ophthalmic examination without the need for restraint or anesthesia, particularly with regard to recording reliable tonometry measurements; and (3) they are pigmented and as such avoid potential confounders present in albino rodents (e.g., Wistar and Sprague–Dawley rats), which have reduced ipsilateral projections.…”
Section: Introductionmentioning
confidence: 99%